Variation in antigenicity and molecular weight of Campylobacter coli VC167 flagellin in different genetic backgrounds. - Alm, R A (1992)
Campylobacter coli VC167 has been shown to undergo a reversible flagellar antigenic variation between antigenic type 1 (T1) and antigenic type 2 (T2). VC167 contains two flagellin genes, and the products of both genes are incorporated into a complex flagellar filament in both antigenic types. Although there are only minor amino acid changes in the flagellins expressed by T1 and T2 cells, the two antigenic types of flagellins can be distinguished by differences in apparent M(r) on sodium dodecyl sulfate-polyacrylamide gels and by immunoreactivity with T1-specific (LAH1) or T2-specific (LAH2) antiserum. The isolation of stable variants of T1 and T2 has allowed for the transfer via natural transformation of the flagellin structural genes from the T1 background into the T2 background and from the T2 background into the T1 background. In addition, the flagellin genes from VC167 T1 and T2 have been transferred into strains of Campylobacter jejuni. The results indicate that the observed antigenic variations of VC167 flagellins are dependent on the host genetic background and independent of the primary amino acid sequence. These data provide evidence that posttranslational modifications are responsible for the antigenic variation seen in VC167 flagellins.